This Must Be the Stage: Staging Popular Music Performance in Italian Media Practices around ’68 - Alessandro Bratus; Maurizio Corbella (Cinéma & Cie, 2018)
Popular music gained increasing cultural relevance in Italy during the Sessantotto (’68) — a tumultuous period essentially extending over a decade, until about 1977. Because of the ideological baggage that performance acquired in those turbulent times, representing performing musicians and the social bodies interacting with them in live contexts became a key challenge for audio/visual media such as cinema, television, radio, and the recording industry. This article attempts an intermedia approach to liveness in mediatized popular music performance by cross-examining the concurrent ways in which two of the above-mentioned media practices — namely film and record production — dealt with the increasing significance and presence of popular music performance in Italian culture at that time. The agency of media as relational frames between performers and the public was strategic in determining the affordance of new popular music genres among young Italian audiences in the 1960s and 1970s. We wish to suggest that the impact of these genres on Italian young audiences reverberated across different media, generating a set of recognizable patterns.